Gramática y poesía: propuestas didácticas* - Martín Rodríguez, Pedro Ángel; Coello Mesa, Antonia M.ª (Didáctica. Lengua y Literatura, 2004)
In this article we try to make an approach to a group of practical alternatives for teaching poems in the classroom in a new creative and active way. Reading and poetic texts will offer us a process for a better understanding and enjoyment of the grammatical learning.